Bandwidth Upgrade in Printed Dipole Antennas Design for LTE Base Station - Rahardian Luthfi Prasetyo; Iswandi Iswandi; Eny Sukani Rahayu (Department of Electrical Engineering and Information Technology,Faculty of Engineering UGM, 2019)
Abstract—In this study the research design development has been carried out by changing the radiating element field width. Radiating element field extension was administered by simulating it and trying to measure the value one by one in antenna simulator software. The radiating element widening was administered so that the resulting bandwidth could be greater. After changing the width of the field, an element radiating field length adjustment was administered to adjust the operating frequency used in Indonesia. After the design worked at the desired frequency and produced a desired bandwidth, antenna fabrication was administered and its results was tested using Mini VNA Tiny to find out the antenna value if mass produced.